The Effect of Nutrition Intervention on Cognitive Function of Children Aged Between 6 and 12 Years – A Study from South India - R, Dr. Anitha.; Raajeswari, Dr. Pa. (Asian Journal of Pharmaceutical Research and Development, 2023)
Nutrition is a fundamental cornerstone of good health, productivity, and overall functional capacity. Food that is safe, plentiful, and nutritious is essential for child growth and development. Children who do not grow properly during childhood may not be able to compensate for the growth loss later in life, even with an adequate diet. This study aimed to evaluate the impact of supplementation of the formulated health mixes which weremade out of selected potential ingredients for undernourished children and nutrition education on child nutrition to their mothers. Based on the inclusion criteria, it is designed as an intervention study with 90 children aged 6 to 12 years. Children were divided into three groups (CG, EGI, and EGII), each with 30 children. The raw materials were obtained, processed, powdered, and blended to create a health mix for three months of supplementation. The children were able to take 50gm of health mix each day as mid-morning and mid-evening snacks in the form of ladoos. The results showed that the children in Experimental Group II who got health mix supplementation as well as health and nutrition education for their mothers improved in nutritional status and cognitive performance. This study provides fresh insights for future policy and intervention programs.